Differential Efficacy Of Isokinetic Training And Conventional Physiotherapeutic Exercise Intervention On Perceived Discomfort And Pain In Osteoarthritis Patients - Naresh Bhaskar, Raj; Srilekha, Saha; Choo Morley, Liza; Hairul Anuar, Hashim (2018)
Present experiment was conducted to investigate the role of Conventional Physiotherapy (CP), Isokinetic Exercise Training (IET) and combined intervention (CI) of CP and IET in reducing pain and stiffness by improving proprioception in participants with knee osteoarthritis. 54 post-menopausal female participants in the age range of 45-65 years with knee osteoarthritis (OA) of Grade II (Kellgren-Lawrence criteria) severity were recruited from the Department of Orthopaedics, Hospital Universiti Sains Malaysia. Participants were subjected to assessment of Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for baseline assessment to evaluate the subjective scale for pain, stiffness and physical function. Deficits in proprioception was assessed employing the isokinetic device BIODEX 4 System. After the baseline assessment, participants were randomly classified into three groups (Gr.) (Viz. Gr. A, Gr. B and Gr. C) and each group comprised of 18 participants. Gr. A participant received CP comprising of strengthening exercises; stretching exercises and range of motion (ROM) exercises. Gr. B received IETraining at velocities of 90 degrees and 150 degrees per second. Gr. C participants received CI training. All the interventions were conducted for 25 - 30 minutes per session; 2 sessions per week for 12 weeks. Mid-term evaluation was done after 6th week followed by the post intervention evaluation after 12th week following pre-intervention analyses protocol. Analyses revealed that interventions were beneficial in improving the strength and proprioception of knee joint in participants with OA of knee joint, which however resulted in reduction of pain and stiffness. For CI and IET participants, pre-intervention level of poor proprioception was found associated with higher extent of pain; stiffness and physical function, which did not improve up to adequate extent. During the post-intervention phase, CP trainees were observed to have better improvement compared to their counterparts in CI and IET, while IET trainees were observed to have no improvement at all. Multiple linear regression analyses revealed the association between pain, level of stiffness and physical function with weight, height and level of proprioception.